The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5902/1980509818841
|View full text |Cite
|
Sign up to set email alerts
|

Fenologia, biometria e precocidade de plantas de caju arbóreo do Cerrado (<i>Anacardium othonianum</i> Rizz.)

Abstract: Fenologia, biometria e precocidade de plantas de caju arbóreo do cerrado (Anacardium othonianum Rizz.) Phenology, biometry and precocity of plants of the arboreous cashew fruit from Cerrado (Anacardium othonianum Rizz.) Resumo O presente trabalho teve como objetivos analisar o comportamento fenológico do caju arbóreo do Cerrado (Anacardium othonianum Rizz.), relacionando a fenologia às condições meteorológicas do período e do local estudado, obtendo-se também dados biométricos das plantas, a fim de selecionar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The Cerrado cashew is widespread in popular medicine, and its accessory fruit is consumed fresh or processed into sweets, jams, liqueurs, juices, ice cream, popsicles, candied fruit, and other products (Belo et al, 2019;Silva et al, 2008). The Cerrado cashew nut (actual fruit) is still narrowly consumed.…”
Section: Grown Here: Characteristics and Potential From Food Of Brazi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Cerrado cashew is widespread in popular medicine, and its accessory fruit is consumed fresh or processed into sweets, jams, liqueurs, juices, ice cream, popsicles, candied fruit, and other products (Belo et al, 2019;Silva et al, 2008). The Cerrado cashew nut (actual fruit) is still narrowly consumed.…”
Section: Grown Here: Characteristics and Potential From Food Of Brazi...mentioning
confidence: 99%
“…When roasted and peeled, the nut is considered a valuable delicacy for its taste and texture. The fruit is rich in energy, carbohydrates, lipids, proteins, minerals, and vitamins (Belo et al, 2019;Silva et al, 2008). Cerrado cashew nuts have more than 50% of fatty acids, comparable to traditional cashew nuts (Alves et al, 2016).…”
Section: Grown Here: Characteristics and Potential From Food Of Brazi...mentioning
confidence: 99%
“…Os ciclos fenológicos de plantas tropicais são pouco estudados (Newstrom et al, 1994) e, além disso, são complexos, apresentando padrões irregulares de difícil reconhecimento, tanto em larga quanto em pequena escala geográfica, principalmente em estudos de curto prazo (Morellato et al, 2000;Morellato, 2002). O conhecimento sobre a fenologia de uma espécie constitui instrumento eficaz de manejo que possibilita reconhecer, por meio da observação dos caracteres morfológicos do indivíduo, o momento fisiológico ao qual se encontram ligadas às necessidades do vegetal que, uma vez atendidas, possibilitarão seu crescimento normal e, consequentemente, boa produtividade (Câmara, 2006;Neves et al, 2010;Belo et al, 2019). Existem diferentes maneiras de estudar estes estádios, como o de Founier (1974) e a escala Biologische Bundesanstalt, Bundessortenamt e Chemische Industrie (BBCH) (BBCH, 2001).…”
Section: Introductionunclassified
“…Em se tratando de espécies com potencial de exploração econômica, como a J. mollissima, é importante elucidar a fenologia dos seus indivíduos. Nesse aspecto, estão envolvidas as fases do crescimento das plantas e o desenvolvimento vegetativo (germinação, emergência, crescimento da parte aérea e das raízes) e reprodutiva (florescimento, frutificação e maturação), delimitando as épocas de ocorrência e as respectivas características (Câmara, 2006;Belo et al, 2019). A escala BBCH foi desenvolvida em 1988 por um grupo composto por cientistas do German Federal Biological Research, Centre for Agriculture and Forestry (BBA), da Federal Variety Authority -Budessortnamant (BSA) e da German National Association of Manufacturer of Agrochemical Products (IVA), criando sistema de codificação unificada para descrever estádios fenológicos de mono e dicotiledôneas (Munger et al, 1998).…”
Section: Introductionunclassified
“…In addition, almost 50% of the biome was devasted by the expansion of agriculture leading to significant losses of genetic diversity (Cohn et al, 2019), mainly from species of the Myrtaceae family (Da Silva et al, 2019;Abreu et al, 2020). Important nutritional traits of native species (e.g., phenolic content and antioxidant activity) make it possible for breeding programs to take advantage of these qualities more quickly (Belo et al, 2019;Barbosa et al, 2022). Studies have shown beneficial interactions between (endophytic) microorganisms and plants, which may also be valuable for agriculture (Tahir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%